2019
DOI: 10.1037/emo0000471
|View full text |Cite
|
Sign up to set email alerts
|

Fear and happiness, but not sadness, motivate attentional flexibility: A case for emotion influencing the ability to split foci of attention.

Abstract: One prominent and consistent effect is that negative emotions with high motivational intensity, such as fear, narrow attention. However, recent data concerning how fear influences vision may suggest that fear could make attention flexible. Thus, the goal of the present study was to examine whether fear, like happiness, enhances attentional flexibility when multiple targets are present in noncontiguous locations. Fear, happiness, or sadness was induced followed by participants completing an attentional task tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
(96 reference statements)
1
12
0
Order By: Relevance
“…Attentional control enables the selection of relevant information and the suppression of irrelevant distractor information. According to the broaden and build theory [30,31], positive affect can change this information selection through a gain in the attentional scope, that is, broadened attention, whereby a larger portion of the visual field is attended [32][33][34][35][36]. Interestingly, there seems to be a trade-off whereby this gain is compensated by increased distractibility.…”
Section: Positive Affect and Attentional Controlmentioning
confidence: 99%
“…Attentional control enables the selection of relevant information and the suppression of irrelevant distractor information. According to the broaden and build theory [30,31], positive affect can change this information selection through a gain in the attentional scope, that is, broadened attention, whereby a larger portion of the visual field is attended [32][33][34][35][36]. Interestingly, there seems to be a trade-off whereby this gain is compensated by increased distractibility.…”
Section: Positive Affect and Attentional Controlmentioning
confidence: 99%
“…Because depression has an impact on the affective and cognitive reactivity of individuals (Guhn, Sterzer, Haack, & Köhler, 2018). Negative emotions with high motivational intensity allow for faster reallocation of attention facilitating detection of potential threats/rewards in one's environment (Storbeck, Dayboch, & Wylie, 2019). Thus, the depressed and the non-depressed people must have some different references to perceive the deadly pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Susskind et al (2008) indicated that when danger was not clearly presented, individuals’ attention was flexible and they searched effectively in peripherical areas. The work of Storbeck et al (2019), meanwhile, pointed out an inconsistency with regard to the link between fear and attention breadth being caused by differences in paradigms, specifically, whether or not the paradigm contained a single clear threatening stimulus (e.g., Finucane, 2011). Storbeck et al (2019) adopted the paradigm with multiple targets in noncontiguous locations.…”
Section: Fear-related Emotions and Holistic Cognitive Stylementioning
confidence: 99%
“…However, fear, as a negative emotion, has also been found to facilitate agile attention that shifts across multiple locations. Storbeck et al (2019) showed that the relationship between fear and attention may be situation-dependent (e.g., whether the danger is certain or not). Thus, there is evidence that points to the alternative possibility that fear is also able to broaden one's visual field.…”
Section: Fear-related Emotions and Holistic Cognitive Stylementioning
confidence: 99%